2022
DOI: 10.1177/09636897221086967
|View full text |Cite
|
Sign up to set email alerts
|

LINC00092 Suppresses the Malignant Progression of Breast Invasive Ductal Carcinoma Through Modulating SFRP1 Expression by Sponging miR-1827

Abstract: Breast invasive ductal carcinoma (IDC) is a most common kind of breast cancer (BC), yet to date the corresponding effective therapies are limited. Extensive evidence has indicated that lncRNAs are involved in multiple cancers, and the potential mechanism of lncRNAs, such as LINC00092, mentioned in IDC remains elusive. IDC clinical samples from TCGA database were used to analyze the expression levels of LINC00092, miR-1827 and SFRP1. Kaplan-Meier method was applied to plot the overall survival curves. KEGG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Wu et al [ 16 ] reported that LINC00092 expression was significantly associated with the survival of BC patients. Zhao et al [ 43 ] discovered that LINC00092 expression was downregulated in breast invasive ductal carcinoma (BIDC) tissues and cells, which promoted malignant progression of BIDC via regulating secreted frizzled related protein 1 (SFRP1) by sponging microRNA-1827. Herein, we revealed that LINC00092 had lower expression level in BC tissues and cells and negatively related to BC tumor size and histological grade, as well as positively related to survival probability of BC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [ 16 ] reported that LINC00092 expression was significantly associated with the survival of BC patients. Zhao et al [ 43 ] discovered that LINC00092 expression was downregulated in breast invasive ductal carcinoma (BIDC) tissues and cells, which promoted malignant progression of BIDC via regulating secreted frizzled related protein 1 (SFRP1) by sponging microRNA-1827. Herein, we revealed that LINC00092 had lower expression level in BC tissues and cells and negatively related to BC tumor size and histological grade, as well as positively related to survival probability of BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a type of ncRNAs with 18-24 nucleotides, microRNAs are main downstream targets of lncRNA [ 66 ]. Zhao et al [ 43 ] reported that LINC00092 sponged microRNA-1827 in BIDC cells to modulate BIDC malignant progression, which implied that LINC00092 regulated BC progression not only by modulating PC expression but also via regulating other molecules. Besides, the in vivo experiment in our research was relatively simple.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00092 is an lncRNA, and has been found to be under-expressed in multiple neoplasms to play the antineoplastic role [15,36]. In TC, only Zhang et al revealed the levels of LINC00092 by analyzing the data from TCGA database [16].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that LINC00092 acts as a sponge for miR-1827. Considering that secreted frizzled-related protein 1 (SFRP1) can directly be targeted by miR-1827, LINC00092/miR-1827/SFRP1 is a signal axis to regulate malignant cell behaviors in IDC (46).…”
Section: Discussionmentioning
confidence: 99%